Presenting A Case with Tubulointerstitial Nephritis and Uveitis (TINU- Syndrome) - E Fotouhi Ardakani; R Azizi; N Nouri-Majalan (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2008)
Concurrence of interstitial nephritis and uveitis named tubulointestitioal nephritis and uveitis syndrome (TINU) are unusual and uncommon presentations of interstitial nephritis. This syndrome is considered after ruling out other differential diagnoses. A-38-year old man presented with acute renal failure and uveitis. The histologic findings of renal biopsy showed acute tubulointestitioal nephritis. The patient had no clinical and paraclinical manifestations of other etiologies of interstitial nephritis and uveitis such as Wegener's granulomatosis , Sjogren's syndrome or sarcoidosis. The diagnosis of TINU-Syndrome was therefore considered. The patient was treated by oral and ophthalmic prednisolone and had a good response to treatment.